Prognostication of noise exposure risk on workers’ safety and health in Lithuania - Butkus, Ričardas; Šarlauskas, Alvidas; Vasiliauskas, Gediminas (Journal of Environmental Engineering and Landscape Management, 2015)
This study explores the association between the levels of noise exposure at various sectors of economic activity and the percentage distribution of workplaces where these levels can occur. The results of the research are based on statistical data which was collected at various workplaces at the sectors of construction, transport, agriculture and forestry, electricity, water and gas supply etc. These results include the mathematical analysis of noise levels at 748 workplaces. These workplaces were sectioned by economic activity sector and percentage distribution was calculated as a ratio between the actual and total number of places where the respective noise level was exceeded. Probability index was calculated as a descriptive parameter for the evaluation of workplaces at various levels of noise exposure level normalized to a nominal 8 hour working day (LEX, 8h). Results show that highest number of workplaces where LEX, 8h was exceeded was at the companies of wood processing and furniture manufacturing. LEX, 8h of 80 dB(A) was exceeded at 77%, LEX, 8h = 85 dB(A) – 72% and LEX, 8h = 87 dB(A) – 68% of all the workplaces. This shows that hearing loss occurrence is likely and it can be assessed as “very risky” or “potentially risky” at the companies of wood, metal and textiles ectors (probability index’s values from 0,087 to 0,032 respectively). First published online: 08 Jul 2014